THE SITUATION OF EXILE PEASANTS - Bakhtiyor Rasulov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the exiled peasants from the Uzbek SSR, their political status, economic and social situation. The author analyzes the situation in most of the displaced persons located in the territory of the country and draws relevant scientific conclusions.